2023
DOI: 10.1093/cercor/bhad143
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of electroencephalographic microstates during sustained pain

Abstract: Brain dynamics can be modeled by a sequence of transient, nonoverlapping patterns of quasi-stable electrical potentials named “microstates.” While electroencephalographic (EEG) microstates among patients with chronic pain remained inconsistent in the literature, this study characterizes the temporal dynamics of EEG microstates among healthy individuals during experimental sustained pain. We applied capsaicin (pain condition) or control (no-pain condition) cream to 58 healthy participants in different sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…As mentioned previously, the attention network is generally considered to be associated with MS-D from a microstate perspective. Recent research has discovered a significant correlation between the duration and coverage of MS-D and pain intensity during sustained pain induced by capsaicin (Qiu et al, 2023). Another study (May et al, 2021) also found fewer occurrences of MS-D in patients with chronic pain.…”
Section: Correlation Between Microstate and Clinical Characteristicsmentioning
confidence: 94%
“…As mentioned previously, the attention network is generally considered to be associated with MS-D from a microstate perspective. Recent research has discovered a significant correlation between the duration and coverage of MS-D and pain intensity during sustained pain induced by capsaicin (Qiu et al, 2023). Another study (May et al, 2021) also found fewer occurrences of MS-D in patients with chronic pain.…”
Section: Correlation Between Microstate and Clinical Characteristicsmentioning
confidence: 94%